The strong correlation between visual function improvement and retinal microcirculation enhancement in glaucoma - Wang, Ting; Ling, Qiying; Shen, Boyu; Jia, Xu (Frontiers in Medicine, 2025)
IntroductionThis study aimed to investigate the alterations in retinal vessel density (VD) among glaucomatous patients following effective intraocular pressure (IOP) reduction and to explore the relationship between retinal VD, visual function, and optic nerve structure.MethodsParticipants diagnosed with primary open-angle glaucoma (POAG) and chronic primary angle-closure glaucoma (CPACG) were included. We measured peripapillary and macular VD, retinal nerve fiber layer (RNFL) thickness, foveal avascular zone (FAZ), and visual field (VF) parameters before treatment, and at 1 week, 1 month, 3 months, and 6 months post-treatment. The data were analyzed using ANOVA and Pearson correlation analysis.ResultsA total of 20 patients were included. Significant improvements in peripapillary VD were observed in the superior and nasal sectors at 1 week, superior and temporal sectors at 1 month, and in the superior, inferior, and temporal sectors at 3 months, with sustained improvements in the superior, nasal, and temporal sectors at 6 months. Recovery of macular VD was noted across all sectors at 1 week, predominantly in the superior parafovea at 1 month, and in the superior, inferior parafovea, and inferior perifovea by 3 months, with further improvement in the inferior parafovea and perifovea at 6 months. The FAZ area significantly narrowed within the first 3 months. The mean deviation (MD) value demonstrated an increase at 1 week, 3 months, and 6 months. Notably, changes in peripapillary VD in the superior and inferior sectors exhibited a strong correlation with MD values, while correlations in the nasal and temporal sectors were moderate. Conversely, the correlation between IOP changes and MD was weak.DiscussionEffective IOP reduction was beneficial for the recovery of both peripapillary and macular microcirculation, leading to improvements in visual function, suggesting that actively improving retinal microcirculation while reducing IOP may contribute to partial recovery of visual function for patients with chronic glaucoma.